Supersaturation is a major driving force for protein aggregation in neurodegenerative diseases - Ciryam, Prajwal (Trends Pharmacol Sci, 2015)
The solubility of proteins is an essential requirement for their function. Yet these ubiquitous molecules can undergo aggregation when the protein homeostasis system becomes impaired. Here we ask which is the driving force for protein aggregation in the cellular environment. Emerging evidence suggests that this phenomenon arises because the native states of many proteins are inherently metastable as their cellular concentrations exceed their critical values. Such `supersaturated' proteins are strongly driven towards aggregation, and are over-represented in specific biochemical pathways associated with neurodegenerative conditions. These observations suggest that effective therapeutic approaches to combat neurodegenerative diseases could be aimed at enhancing the ability of the cell to maintain protein solubility.